UV-optical colors as probes of early-type galaxy evolution - Kaviraj, S; Schawinski, K; Devriendt, J; Ferreras, I; Khochfar, S; Yoon, S; Yi, S; Deharveng, J; Boselli, A; Barlow, T; Conrow, T; Forster, K; et al. (American Astronomical Society, 2007)
We have studied ~2100 early-type galaxies in the SDSS DR3 which have been detected by the GALEX Medium Imaging Survey (MIS), in the redshift range 0 < z < 0.11. Combining GALEX UV photometry with corollary optical data from the SDSS, we find that, at a 95% confidence level, at least ~30% of galaxies in this sample have UV to optical colors consistent with some recent star formation within the last Gyr. In particular, galaxies with an NUV − r color less than 5.5 are very likely to have experienced such recent star formation, taking into account the possibility of a contribution to NUV flux from the UV upturn phenomenon. We find quantitative agreement between the observations and the predictions of a semianalytical ΛCDM hierarchical merger model and deduce that early-type galaxies in the redshift range 0 < z < 0.11 have ~1%-3% of their stellar mass in stars less than 1 Gyr old. The average age of this recently formed population is ~300-500 Myr. We also find that "monolithically" evolving galaxies, where recent star formation can be driven solely by recycled gas from stellar mass loss, cannot exhibit the blue colors (NUV − r < 5.5) seen in a significant fraction (~30%) of our observed sample.